Acute otitis media in children presenting to the emergency department: Is it diagnosed and managed appropriately?. (20th February 2019) - Balasundaram, Niroshan; Phan, Dung; Mazzoni, Daniel; Duong, Elliot; Sweeny, Amy; Del Mar, Chris; Keijzers, Gerben
Abstract : Aim: To describe the diagnostic and management practice in children with acute otitis media (AOM) presenting to the emergency department (ED) and compare diagnosis and management against existing guidelines. Methods: We performed a retrospective descriptive cohort study of patients ≤15 years of age who presented to two EDs in Southeast Queensland between January 2016 and June 2017 with an ED diagnosis of AOM. Likelihood of diagnosis was based on medical records and classified as likely, possible or unlikely using paediatric practice guidelines. Appropriateness of antibiotics prescription was classified using the National Antibiotic Prescribing Survey, which takes into account adherence to the Australian Therapeutic Guidelines. Each medical record was extracted by two blinded reviewers, and discrepancies were resolved by consensus or arbitration. Results: Of the 305 patients included for analysis, 87% had a likely or possible diagnosis of AOM. Otalgia was the presenting complaint in 75%. Standard otoscopy was the routine method for tympanic membrane visualisation, and 70% had abnormal tympanic membrane findings. Almost two‐thirds (62%) of all children were prescribed antibiotics. Antibiotic appropriateness could be ascertained for 286 patients (94%). A total of 39% received inappropriate antibiotic management for AOM. The majority of patients received analgesia in the form of paracetamol and/or ibuprofen. Conclusions: ED clinicians make the diagnosis of AOM fairly accurately, although better assessment of the tympanic membrane by tympanometry and/or pneumatic otoscopy may improve accuracy. More than one‐third of patients are prescribed antibiotics inappropriately. Our data can inform knowledge translation and education strategies to ensure the correct evidence‐based management of this condition.